Collapse in the endurance athlete - Sallis, R. (Sports Science Exchange, 2004)
About collapse in sports which is perhaps the most dramatic of all medical problems affecting athletes. Though collapse can be seen in any athletic event requiring maximal exertion, it is most common in endurance events, such as marathons and triathlons. The incidence seems to increase as the race distance, temperature, and humidity increase. Content: - Defining Exercise-Associated Collapse - Evaluation of the Collapsed Athlete in the Field - Drugs that can adversely affect thermoregulation - Severity Classification for the Collapsed Athlete - Causes of Collapse in the Endurance Athlete.